2014
DOI: 10.1128/jvi.02125-14
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Mechanisms Regulate Exposure of Neutralizing Epitopes in the V2 and V3 Loops of HIV-1 Envelope

Abstract: Broadly neutralizing antibodies targeting the HIV-1 envelope (Env) are key components for protection against HIV-1. However, many cross-reactive epitopes are often occluded. This study investigates the mechanisms contributing to the masking of V2i (variable loop V2 integrin) epitopes compared to the accessibility of V3 epitopes. V2i are conformation-dependent epitopes encompassing the integrin ␣4␤7-binding motif on the V1V2 loop of HIV-1 Env gp120. The V2i monoclonal antibodies (MAbs) display extensive cross-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
59
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

8
2

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 79 publications
(91 reference statements)
9
59
0
Order By: Relevance
“…The neutralization levels attained were significantly higher than the calculated sums of percent neutralization attained by each MAb alone and CD4. The other V3 MAbs, 2219 and 2557, were similarly affected by CD4 (54). These data indicate that CD4-induced conformational changes modulate MAb accessibility of the 2424 epitope, similar to the other neutralizing V3 epitopes.…”
Section: To 5)supporting
confidence: 49%
“…The neutralization levels attained were significantly higher than the calculated sums of percent neutralization attained by each MAb alone and CD4. The other V3 MAbs, 2219 and 2557, were similarly affected by CD4 (54). These data indicate that CD4-induced conformational changes modulate MAb accessibility of the 2424 epitope, similar to the other neutralizing V3 epitopes.…”
Section: To 5)supporting
confidence: 49%
“…Deletion of V1V2 leads to a better exposure of V3 epitopes and thus better neutralization by V3 mAbs (101,102). Importantly, it was recently shown that anti-V3 Abs are effective against tier 2 viruses if the Ab and virus are coincubated for several hours rather than for 1 to 2 hours, which is the norm in standard neutralization assays (103). These results suggest that the V3 loop is meta-stable on the virus surface, flickering between a cryptic and exposed conformation, the latter being both required for interaction with the chemokine receptor and available for Ab binding leading to neutralization.…”
Section: Glycan-independent "Ladle-like" V3 Absmentioning
confidence: 58%
“…We assessed the neutralizing activity of all immune sera from experiment H3 using the TZM.bl assay under conditions in which the virus and sera were incubated together for either 30 min or 24 h prior to addition to cells, as per previous studies (53); the pseudoviruses of strains MW965 and ZM109 were used (Table 4 and Fig. 6, respectively).…”
Section: Resultsmentioning
confidence: 99%